MAPPING CONTEMPORARY ISLAMIC JURISPRUDENCE OF MUḤAMMAD SAʻĪD AL-‘ASHMĀWĪ AND MUḤAMMAD SHAḤRŪR - Yusroh, Yusroh; Abd. Rahman, Mohd. Zaki (Universitas Ahmad Dahlan, 2018)
Muḥammad Saʻīd Al-‘Ashmāwī and Muḥammad Shaḥrūr are well known as contemporary Muslim thinkers. This article tries to map their contemporary ideas on Islamic jurisprudence. The main data of this research taken mainly from the works both of Al-‘Ashmāwī and Shaḥrūr. In particular, the paper tries to analyze Al-‘Ashmāwī‘s ideas on sharia, politics, hijab, marriage and divorce. On the other hand, the ideas of Shahrour on al-Qur'an, Sunnah and Fiqh, the theory of borders, pluralism, the commandment, inheritance, hijab, marriage, divorce, dowry, politics, and imamate are also critizised. After analyzing their lives and their ideas on Islamic jurisprudence, the paper found that their social, educational and practical backgrounds have affected their intellectual formations and ideas. Ashmawi is encouraged by diligence and enlightenment and is believed to be enlightened. Shahrour, however, takes a new approach in order to create the ḥudūd theory as a new way. As well as their intellectual background, Ashmawi has a good queen in Arabic, English and French as well as religion, Sharia, jurisprudence and theology. Shahrour is a good queen in Arabic, English, Russian, philosophy, philology and historical language.